Determination of doxazosin and verapamil in human serum by fast LC-MS/MS: application to document non-compliance of patients - Chytil, Lukáš; Strauch, Branislav; Cvačka, Josef; Marešová, Věra; Widimský, Jiří; Holaj, Robert; Slanař, Ondřej (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2010)
A rapid and sensitive method using liquid chromatography-tandem mass spectrometry (LC-MS/MS) for simultaneous determination of doxazosin and verapamil in human serum has been developed. Trimipramine-d₃ as an isotopic labelled internal standard was used for quantification. Serum samples were prepared by simple liquid-liquid extraction with mixture of tert butyl methyl ether and ethyl acetate (1:1, v:v). The analytes and internal standard were separated on C18 column using an isocratic elution with 5 mM ammonium formate with 0.02% formic acid and 0.02% formic acid in acetonitrile (55:45, v:v) at a flow rate of 1.1 mL/min. Positive TurboIonSpray mass spectrometry was used with multiple reaction monitoring of the transitions at: m/z 455.3→165.2 and 150.2 for verapamil, m/z 452.2→344.4 and 247.4 for doxazosin, m/z 298.2→103.1 for trimipramine-d₃. Linearity was achieved between 1 and 500 ng/mL (R² ≥ 0.997) for both analytes. An extensive pre-study method validation was carried out in accordance with FDA guidelines. This assay was successfully applied to determine the serum concentrations of doxazosin and verapamil in suspect non-compliance patients.
Keywords: Chromatography, Liquid; doxazosin; Doxazosin; Tandem Mass Spectrometry; antihypertenziva; Verapamil; Patient Compliance; adherence pacienta; lidé; chromatografie kapalinová; tandemová hmotnostní spektrometrie; Humans; Antihypertensive Agents; verapamil; Hypertension; hypertenze